In situ XRD investigation of Cu2ZnSnSe4 thin film growth by thermal co‐evaporation. Issue 9 (9th January 2014) - Kaune, Gunar; Hartnauer, Stefan; Scheer, Roland
<x xml:space="preserve">Abstract</x> The deposition of a Cu2ZnSnSe4 (CZTSe) thin film with a multi‐stage co‐evaporation process is investigated with time‐resolved in situ X‐ray diffraction (in situ XRD). For the experiment a novel setup intended for in situ analysis of thin film deposition processes was used. The in situ data confirm the former observation that CZTSe growth is delayed with deposition of only Cu2−xSe and ZnSe in the initial process stage and provide new insight into the evolution of the appearing phases. In Zn‐rich deposition conditions, ZnSe deposited at the beginning may not be consumed by the growing CZTSe but remain as an unreacted layer at the interface to the Mo back contact. Cu2−xSe growth starts with the formation of a Cu rich phase, which is reduced to a Cu poor phase in the process. Furthermore, our results show that in situ XRD at elevated temperatures is able to distinguish between ZnSe and CZTSe and that it can be used for the detection of ZnSe as secondary phase.